Dampak Sakit Hati Ditinjau dari Kisah Hidup Tokoh Ahitofel (Lembaga Pengembangan Kinerja Dosen, 2025)
Heartache can cause great stress. This stress affects feelings emotionally, physically, and overall health. Although emotional, heartache apparently does not only make someone feel sad, angry, or disappointed. Some of those who experience it even feel that heartache also has a bad impact on their physical condition. Heartache is not only detrimental to oneself, but also to family and those around them. Ahithophel is a figure who is famous for his wisdom and understanding but became a victim of heartache. Ahithophel is known as King David's advisor. Ahithophel served David since the beginning of his reign in Hebron and was close to him for many years. Suddenly he opposed King David and joined the conspiracy of Absalom, King David's son, who seized the throne. Then because his advice was not obeyed by Absalom, he hanged himself.